A study on assessment of socio-demographic characteristics and pattern of health-care support among geriatric people residing in old age homes, Nandyal - Geetha, Dugavath; Pasha, M. A. Mushtaq; Fatima, Afsar (International Journal Of Community Medicine And Public Health, 2021)
Background: Geriatric age is one of the vulnerable phases of life. Geriatric population in India is faster growing share of population with more special needs for health-care and support. Objective was to study the socio-demographic factors and assess pattern of health care support among geriatrics residing in old age homes, Nandyal. Methods: This was a cross-sectional study among geriatric people aged more than 60 years residing in old age homes, Nandyal from October 15, 2019, to December 15, 2019. One hundred eighty participants were included. Those who were not present during the analysis were excluded from the class using convenience sampling. Data was collected using a pre-designed, pre-tested, semi-structured questionnaire and analysing data using SPSS version-22. Results: Around 180 subjects, 76 (42%) of the elderly received treatment for their morbidities from private clinic and hospitals, while 37.8% from government hospitals. Children bear health care expenses for 32 (17.5%) of the elderly. Among 84 (46.7%) of elderly dependent on their social security schemes. while 30 (16%) had health insurance. Around 72 (40%) of elderly financially dependent on their children. Major complaints are Arthritis (47.7%) followed by hypertension (20%) and acid-peptic disease. Conclusions: A high prevalence of arthritis, hypertension and acid peptic disease were identified. It also highlighted that economic independence and the use of social security schemes among elderly is less. Based on these findings recommended that there is a need to develop financial assistance and social security schemes are needed to enhance health care facilities, economic independence and utilization services.